2017
DOI: 10.1111/vop.12463
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressure in American Bullfrogs (Rana catesbeiana) measured with rebound and applanation tonometry

Abstract: The rebound tonometer is the preferable tonometer for American Bullfrogs. Neither tonometer produced IOP readings that matched the manometer. The rebound tonometer was more precise and it was faster and easier to use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
1
7
0
2
Order By: Relevance
“…5 for dogs and cats resulted in values well in accordance with the manometrically-derived, actual IOP. In the second part of the study, a total of 94 dogs (188 eyes) and 64 cats (128 eyes) were examined.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…5 for dogs and cats resulted in values well in accordance with the manometrically-derived, actual IOP. In the second part of the study, a total of 94 dogs (188 eyes) and 64 cats (128 eyes) were examined.…”
supporting
confidence: 82%
“…Referenzwerte für den TPA fehlen bislang für Hunde und Katzen. Es wurden bisher Messungen bei Kaninchen, Nordamerikanischen Ochsenfröschen, Rindern, Ziegen und Schafen vorgenommen [5][24] [25].…”
Section: Methodsunclassified
See 1 more Smart Citation
“…Several studies have reported ocular disease in anurans, but only one clinical review reported normal ocular morphology . Two recent studies have evaluated IOP values in different frog species. To the authors’ knowledge, no studies have been performed documenting the normal ocular morphology of PGF's.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on various species have validated the use of the Tonovet through correlation with manometry, [18][19][20][21][22] but no rebound tonometer has been validated in an anuran species. Cannizzo et al 11 created calibration curves for both Tonovet and TonoLab in American Bullfrogs, but neither tonometer produced IOP readings that matched the manometer. Two studies 23,24 have evaluated tonometry in anurans using the Tonovet in the "d" setting.…”
mentioning
confidence: 99%